Identitas genetik Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) dari daerah endemik penyakit kuning cabai di Indonesia bagian barat berdasarkan fragmen mitokondria sitokrom oksidase I (mtCOI) - Sat Rahayuwati; Sri Hendrastuti Hidayat; Purnama Hidayat (Perhimpunan Entomologi Indonesia, 2016)
Bemisia tabaci (Gennadius) is an important horticulture pest and is know to be a vector of Geminivirus. Pepper yellow leaf curl Indonesia virus (PYLCIV) is caused by Geminivirus, know to be transmitted by B. tabaci. It became an important disease in pepper and could cause 100% yield loss. Currently there is limited information concerning the genetic of B. tabaci associated with Geminivirus in Indonesia. It is therefore important to investigate the genetic identity of B. tabaci across different population. The aim of this research was to investigate the genetic identity of B. tabaci that were collected from pepper yellow leaf curl endemic area in the western part of Indonesia. Research activities include 1) sample collection of B. tabaci from pepper yellow leaf curl endemic area in west Indonesia; 2) single extraction of B. tabaci total DNA; 3) amplification of mitochondrial Cytochrome Oxidase I gene (mtCOI) fragmen with polymerase chain reaction (PCR); 4) mtCOI sekuencing 5) phylogenetic analysis of mtCOI fragmens from west Indonesian PYLCIV compared with some B. tabaci mtCOI deposited in National Center for Biotechnology Information (NCBI). Based on mtCOI fragment analysis, B. tabaci from PYLCIV endemic area were in one group belong to Asia I clusters. Genetic identity of B. tabaci from endemic area in Western Part of Indonesia were similar with polyatomic cladogram.